Immunoscreening of a cutaneous T-cell lymphoma library for plasma membrane proteins - Lee-Theilen, Mieun; Schadendorf, Dirk; Eichmüller, Stefan B. (Cancer immunology immunotherapy, 2007)
Cutaneous T-cell lymphomas (CTCL) belong to non-Hodgkin lymphomas, which are primarily manifested in the skin and mostly exhibit a T-helper memory phenotype. Mycosis fungoides (MF) and the leukemic variant Sézary syndrome (SzS) are the most common forms of CTCL. The aim of this study was to identify CTCL surface proteins with a tumor specific expression profile. A plasma membrane enriched fraction of the CTCL cell line HuT78 was used for immunization of two rabbits. Subsequently, a CTCL cDNA phage library was screened by a new variant of the SEREX method (serological identification of antigens by recombinant expression cloning) using the polyspecific rabbit antisera instead of patients’ sera. Isolated reactive transfectants were sequenced and 42 different genes identified including four known plasma membrane proteins: Ligatin, HLA-A, integrin α4 and MT5-MMP. The level of transcripts of the matrix metalloproteinase MT5-MMP was diminished in MF tumor specimens. MT5-MMP normally occurs in several different protein variants. Western blot analysis revealed that activated MT5-MMPs were reduced in tumor specimens, whereas the amounts of most of the inactivated variants were unchanged. The amount of mRNA coding for the adhesion protein integrin α4 was not altered in tumor specimens in comparison to controls when analyzed by quantitative real-time PCR analysis. Ku86, known to be predominantly located in the nucleus and cytosol, was frequently detected during the SEREX screening. Western blot analysis revealed higher protein amounts of Ku86 in HuT78 than in control cells. In addition, we could show, that Ku86 can also be detected in lipid rafts of CTCL cells as it has been described for other tumor types. Thus, Ku86 might be involved in homo- and heterotypic adhesion steps of CTCL tumor cells and might protect these cells against apoptosis triggered by irradiation as it was suggested for multiple myeloma cells. The design of this study enabled screening for all proteins on the plasma membrane, irrespectively of whether these are directly anchored within the membrane or associated with other membrane proteins. Further analysis will unravel whether the list of identified proteins harbors candidates, which might be accessible for antibodies from outside the cell.